Being a woman, young and hiker: Gender memories and moral panic in perceptions of hiking - Caro Cárdenas, Ricardo (2006)
At the entrance to the cemetery in the city of Huamanga, there is a tombstone that is particularly striking. Unlike the others, it has a poem inscribed on it, it almost never lacks flowers, and it is not strange to see someone stop to look at it. It is the tomb of Edith Lagos, who was buried in that place, shortly after her body was moved from Andahuaylas and crossed a large part of the city, in the most massive and apparent manifestation of sympathy towards the senderista subversion that the country suffered. This famous young hiker was assassinated in 1982, a few months before the department of Ayaucho came under military control for almost two decades.